Resolution of Religion Conflicts Through Communication Strategies in Gharib Fil Ma'na Hadiths - Azzuhri, Muhandis; Farmawati, Cintami; Amalia, Zahida Putri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Religious conflicts are often caused by misunderstandings arising due to mismatch in the ways of communication. Effective communication along with a sincere desire to resolve conflicts will be more likely to make resolution of religious conflicts successful. The focus of this study is to describe religious conflict resolution through the communication strategy of the Prophet Muhammad in the hadiths